History Patient Medical Record Health Systems Using UML Modeling For Information Technology Online Implementation - Rahmawati, Elmi (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2016)
This research is conducted to analyze the medical records patient where these data areprocessed using UML it aims to getting a proper diagnose of patients drugs use in accordance with his disease .In this study author uses the method of observation and interviews to obtion data that writers need. Data that has been applied writer get backed into a website with php programming language .So with this websiteÂ servies patients who where at theÂ POSKESKEL to see her medical record online , with the sense of patients had suffered the same can use drugs have been is in medical record patients.